GE_GERICHTE P/2213/2020 vom 27. August 2021 - GE Cour de justice (2021)
FIXATION DE LA PEINE;PEINE PRIVATIVE DE LIBERTÉ;AMENDE | LStup.19.al1.letc; LStup.19.al1.letd; CP.47; LEI.115.al1.letb; LStup.19a.ch1; CP.49.al1; CP.41.al1; CP.106